Proton conduction of an ionic HOF with multiple water molecules and application as a membrane filler in direct methanol fuel cells - Zhao, Fang; Cao, Li-Hui; Ji, Can (Journal of materials chemistry. C, Materials for optical and electronic devices, 2023)
Owing to their clean and green energy, fuel cells are considered to be one of the most environmentally friendly technologies for achieving the conversion of chemical and electrical energy. Direct methanol fuel cells (DMFCs) have attracted much attention due to their light weight, compactness and high energy density. In this work, an ionic hydrogen-bonded organic framework ( iHOF-8 ) with a dense 2D hydrogen-bonded network was synthesized from 1,3,5-tris[(4-sulfonyl)phenyl] benzene (H 3 SPB) and 1,1′-diamino-4,4′-bipyridine diiodide (DBpy·2I). The proton conductivity of iHOF-8 could reach 5.02 × 10 −3 S cm −1 at 98% RH and 100 °C. Furthermore, Nafion composite membranes with different iHOF-8 doping contents were also prepared. The 9%-iHOF-8/Nafion membrane could realize an ultrahigh proton conductivity of 1.6 × 10 −1 S cm −1 at 98% RH and 100 °C, which is 2.58 times larger than that of the recast Nafion. In particular, the 9%-iHOF-8/Nafion composite membrane was used as the solid electrolyte for DMFC tests. The results showed that the 9%-iHOF-8/Nafion composite membrane had a maximum power density of 73.5 mW cm −2 and a maximum current density of 599.4 mA cm −2 , which are 1.47 and 1.80 times higher than those of the recast Nafion, respectively. This work indicates that the 9%-iHOF-8/Nafion membrane has great promise as a PEM for DMFCs and can be potentially applied in future energy conversion devices. The proton conduction properties of iHOF-8 and its Nafion-based composite membrane were investigated and the results proved to be of potential value in DMFCs.